Iowa RBA, May 15-17, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for May 15-17, 1995. Highlights of the update include sightings of a Laughing Gull, the continued presence of a Red-necked Phalarope and White-faced Ibis, King Rail, Black-headed Grosbeak and two Mississippi Kites. Epson - sheet feed/flatbed